Adaptation of Candida albicans to commensalism in the gut. (April 2016) - Prieto, Daniel; Correia, Inês; Pla, Jesús; Román, Elvira
Candida albicans is a common resident of the oral cavity, GI tract and vagina in healthy humans where it establishes a commensal relationship with the host. Colonization of the gut, which is an important niche for the microbe, may lead to systemic dissemination and disease upon alteration of host defences. Understanding the mechanisms responsible for the adaptation of C. albicans to the gut is therefore important for the design of new ways of combating fungal diseases. In this review we discuss the available models to study commensalism of this yeast, the main mechanisms controlling the establishment of the fungus, such as microbiota, mucus layer and antimicrobial peptides, and the gene regulatory circuits that ensure its survival in this niche.